Hubungan Keleluasaan Pemberian Gadget Dengan Mental Emosional Anak Usia 3 – 5 Tahun di TK Kartika Kabupaten Lumajang - Novenda Eka Putri Safira; Yessy Nur Endah Sary; Iit Ermawati (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
can have a negative impact, if their use is not in accordance with the recommendations from the American Academy of Pediatrics (AAP). The purpose of this study was to determine a significant correlation between the freedom to give gadgets and the emotional mentality of children aged 3-5 years at Kartika Kindergarten, Lumajang. The cross-sectional research design was used with 40 respondents at Kartika Kindergarten, Lumajang Regency. The measuring tools in this study are the KMME questionnaireand the use of gadgets. Spearman's rho test was used to answer the purpose of this study. The results showed that the majority of mothers gave gadgets to children in the good category, 28 respondents (70%). The majority of emotional and mental children aged 3-5 years are in the normal category as many as 37 respondents (92.5%). There is a significant correlation between the flexibility of giving gadgets and the emotional mentality of children aged 3-5 years in Kartika Kindergarten, Lumajang, namely p- value 0.001. .